CULTURAL APPROACH IN FOREIGN LANGUAGE CLASSES - Kodirov Umut Ruziboyovich (European Science Publishing, 2025)
Teachers focus on students’ professional acquisition of different languages at the university. The article describes the process of foreign language acquisition in non-linguistic classes. The main idea in this process is to develop students' ability to speak languages of different cultures in the direction of their future professions, taking into account the intercultural approach. It is important to connect a professional approach to education with cultural background. It should be closely related to the bright components of culture: stereotypes, clothing, eating habits, behavior, etc. Students want to learn how to become aware of specific strategies for intercultural communication. We live in a colorful world and relationships with representatives of other cultures are very important. Culture affects both verbal and non-verbal communication. Learning a foreign language in the cultural center is of particular importance. Cultural immersion helps students effectively understand professional, business, and academic issues and successfully communicate with foreign colleagues. They also try to understand business issues from a cultural perspective and present themselves as equal partners in global processes.
Keywords: Culturology, linguoculturology, culturological approach, foreign language, acculturation, problem situation, sociocultural approach, communicative-ethnography, content analysis, comparative studies.